2016
DOI: 10.5897/ajar2016.11425
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nitrogen and phosphorus from cattle farming wastewater using constructed wetland system

Abstract: The confined dairy cattle system employs the most modern production techniques with respect to the genetic standards of the herds. The success found in these systems promoted an increase in the number of confined animals and, consequently, an increase in the produced volume of waste, causing the waste from dairy cattle farming to be one of the largest problems in intensive management systems. This effluent has high amount of phosphorus and nitrogen, and the accumulation of these nutrients in surface waters can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Most wetland units degrade nutrient-type pollutants such as ammonia, phosphorus, and residual organic substances from previous processing (Geovana et al, 2016;Moenir et al, 2014;Marlena et al, 2018;Setianingsih et al, 2021). However, the high concentration of oil & grease pollutants and MBAS will be more effectively degraded under aerobic conditions (Primasari et al, 2011).…”
Section: Performance Of Removal Pollutantmentioning
confidence: 99%
“…Most wetland units degrade nutrient-type pollutants such as ammonia, phosphorus, and residual organic substances from previous processing (Geovana et al, 2016;Moenir et al, 2014;Marlena et al, 2018;Setianingsih et al, 2021). However, the high concentration of oil & grease pollutants and MBAS will be more effectively degraded under aerobic conditions (Primasari et al, 2011).…”
Section: Performance Of Removal Pollutantmentioning
confidence: 99%
“…Unit Wetland digunakan untuk mereduksi kadar nitrogen organik didalam air limbah. Lahan basah buatan (constructed wetland) adalah sistem yang dirancang dan dibangun dengan memanfaatkan proses alami yang melibatkan vegetasi lahan basah, tanah, dan mikroba untuk membantu pengolahan air limbah (7) . Kemampuan penurunan Nitrogen industri pengolahan lele di unit wetland telah dibahas tersendiri secara spesifik di mana kemampuan penurunan ammonia di wetland mencapai 87,34% (8) , Kemampuan wetland dalam menurunkan ammonia, nitrat dan nitrit di beberapa industry juga telah dibahas dalam paper yang ditulis oleh Lamchaturapatr dan Vymazal (9; 10) .…”
Section: Latar Belakangunclassified
“…Existing studies have found that CWs are mainly used in the treatment of organic wastewater such as landfill leachate [5], rural sewage [6], and aquaculture wastewater [7]. The main treatment indexes include chemical oxygen demand (COD), ammonia nitrogen (NH4-N) [8], total nitrogen (TN) [9], total phosphorus (TP) [10], and other pollutants, while there are relatively few studies on heavy metal wastewater [11]. It is speculated that the main reason is the poor removal of heavy metals by CWs, the less adsorption of substrates, the slow enrichment effect of plants, and the long treatment period, resulting in the limited application of CWs in the purification of heavy metal wastewater [12].…”
Section: Introductionmentioning
confidence: 99%